Philippe Herreweghe conducts Bach's Christmas Cantatas Collegium Vocale Gent - Bach, Johann Sebastian; Bach, Johann Sebastian; Bach, Johann Sebastian; Bach, Johann Sebastian (Arte France and Prismedia, 2015)
Get in the Christmas spirit with Philippe Herreweghe, the Collegium Vocale Gent, and its period-instrument orchestra in a concert filmed on December 23, 2015 at Paris's beautiful Église Saint-Roch! Joined by soprano Dorothee Mields, countertenor Damien Guillon, tenor Thomas Hobbs, and bass Peter Kooij, they perform four seasonal cantatas from J.S. Bach's time in Halle and Leipzig. Composed in 1734 for six major religious feast days, Bach's six Christmas Oratorio cantatas count together as one of his most popular sacred works, performed every December throughout Germany and around the world. But before he wrote the Christmas Oratorio, Bach had already spent many years composing individual cantatas for the Sundays of the Christmas season, from the beginning of Advent through to Epiphany. This program features four effervescent cantatas from those earlier years: one cantata from his time in Weimar (Christen, ätzet diesen Tag, BWV 63 for Christmas Day, 1713) and three cantatas from his first two years in Leipzig (Darzu ist erschienen der Sohn Gottes, BWV 40 for December 26, 1723; Nun komm, der Heiden Heiland, BWV 62 for December 3, 1724, and Gelobet seist du, Jesu Christ, BWV 91 for December 25, 1724). With festive brass, spritely oboes, and melodious strings, these works joyfully sing out the good news of the Savior's arrival and offer reflective commentary on how the faithful can prepare themselves. This first-rate performance incarnates the beauty and drama of Bach's music, and bears witness to the eminent reputation of Herreweghe and his accomplished musicians of the Collegium Vocale Gent